Looking Both Ways At the Intersection of the Academy and the Church: ​Essays in Honor of Joseph C. Grana II - Holtzen, Wm. Curtis (Claremont Press, 2021)
This volume explores a variety of topics in biblical studies, ministry, and pedagogy from perspectives inspired by Joseph Grana II.